Development and Measurement of 5 kN Âµ-Forming Machine - Mahmudah, Aida (University of Muhammadiyah Malang, 2016)
The need of micro part become increasingly popular which make increase of the need of prodution technology with high accuracy, productivity, efficiency, and reliability.Metal forming technology offers the solution to answer the challenge. High produtivity, zero material losses, good mechanical properties of product, and tight tolerance is able to achieve by micro forming technology. This thing make metal-forming fit for mass production based on near net shape technology concept it offered.Miniaturized effect phenomena which was not simple on micro-scale manufacturing process, demand high accuracy level from all aspect of micro-manufacturing process, which are material, tool, machinery and process. Therefore, characteristic of micro-forming machine become important in defining reliability of micro-forming system.Â Micro-forming machine under investigation was 5 kN m-Forming Machine developed in Manufacturing Laboratory, Department of Mechanical Engineering, Universitas Indonesia. Modification to the machine made changes on machine characteristic. Therefore, it need characterization of the machine by measuring its geometric measurement and linear movement. The research revealed that deviation caused by imperfection of geometry of assembled machine component shown good results. Testing of linear movement of machine in one cycle show the range of deviation was 0.024 mm with smallest deviation was -0.0135 mm while the biggest one was 0.0105 mm.Â The value of deviation was below etimated value which estimated from mathematical analisys of backlash. The results of machine linear movement also gave reccomendation of effective path of 5 kN m-Forming Machine, which is on path along 30 mm to 40 mm, from point A which had been decided before.